2021
DOI: 10.1002/anie.202101986
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold‐Directed Face Selectivity Machine‐Learned from Vectors of Non‐covalent Interactions

Abstract: This work describes a method to vectorize and Machine-Learn, ML, non-covalent interactions responsible for scaffold-directed reactions important in synthetic chemistry. Models trained on this representation predict correct face of approach in ca. 90 % of Michael additions or Diels-Alder cycloadditions. These accuracies are significantly higher than those based on traditional ML descriptors, energetic calculations, or intuition of experienced synthetic chemists. Our results also emphasize the importance of ML m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…[6] In this area, Sigmansmulti-variant linear regression approach [10] has reached remarkable success in the predictive modelling of asymmetric transformations. Using machine learning (ML) strategies,independent studies from Denmark, [11] Sunoj, [12] Corminboeuf [13] and Grzybowski [14] have shown that AI model is able to capture the statistical pattern of chiral induction and achieve accurate enantioselectivity prediction in stereoselective synthesis.I n addition, as eries of innovative ML technologies have been applied in the prediction of reactivity, [15] chemo- [16] and regioselectivity [17] of organic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In this area, Sigmansmulti-variant linear regression approach [10] has reached remarkable success in the predictive modelling of asymmetric transformations. Using machine learning (ML) strategies,independent studies from Denmark, [11] Sunoj, [12] Corminboeuf [13] and Grzybowski [14] have shown that AI model is able to capture the statistical pattern of chiral induction and achieve accurate enantioselectivity prediction in stereoselective synthesis.I n addition, as eries of innovative ML technologies have been applied in the prediction of reactivity, [15] chemo- [16] and regioselectivity [17] of organic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…While logistic regression is an established ML technique, it is underutilized in organic chemistry. 38,39,40 The algorithm identified a bivariate classification using buried volume and total ligand dipole (Fig. 5A, graph 2 and Fig.…”
Section: Multi-objective Optimizationmentioning
confidence: 99%
“…Many useful reactions are underutilised in synthetic organic chemistry because of an inability to predict the regioselectivity of the reaction, 1 and there is thus an increasing interest in developing regioselectivity prediction methods for such reactions. Recent examples include nucleophilic 2,3 and electrophilic aromatic substitution reactions, 4–9 Diels–Alder reactions, 10,11 Heck reactions, 12 radical C–H functionalisation of heterocycles, 13 and reactions such as alkylations, Michael additions, and aldol condensations that proceed through proton abstraction. 14 These methods have been based on either quantum chemical (QM) calculations, 2,5,6 machine learning (ML) trained on experimental data, 8,10–12 or a combination of the two where QM has either provided descriptors for the ML model 3,9 or was used to augment the training data.…”
Section: Introductionmentioning
confidence: 99%
“…Recent examples include nucleophilic 2,3 and electrophilic aromatic substitution reactions, 4–9 Diels–Alder reactions, 10,11 Heck reactions, 12 radical C–H functionalisation of heterocycles, 13 and reactions such as alkylations, Michael additions, and aldol condensations that proceed through proton abstraction. 14 These methods have been based on either quantum chemical (QM) calculations, 2,5,6 machine learning (ML) trained on experimental data, 8,10–12 or a combination of the two where QM has either provided descriptors for the ML model 3,9 or was used to augment the training data. 13,14 However, these approaches have rarely been compared on the same dataset.…”
Section: Introductionmentioning
confidence: 99%